Analysis of New Business Opportunities from Online Informal Education Mediamorphosis Through Digital Platforms - Cicilia Sriliasta Bangun; Suryari Purnama; Aropria Saulina Panjaitan (International Transactions on Education Technology (ITEE), 2022)
The existence of digital and online-based technologies has aided in societal upheaval. This also altered the dynamics of the education industry, allowing it to influence the growth of digitalization, which became a watershed moment in the Industrial Revolution. 4.0. Because today's learning material is relatively accessible to get through Video On Demand on the internet, the presence of formal education is beginning to gain popularity. Although, with the advent of the virtual learning paradigm, more and more institutions are providing informal education. Take advantage of this chance to give informal education for new business prospects. The researchers discovered, using Mediamorfosis Theory, that the convergence of informal education has modified the pattern of learning that is connected to technical skill for audiences who have a high level of education.